2006
DOI: 10.1002/pssb.200672567
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of the optical properties of wurtzite and rock‐salt Zn1–xCoxO thin films

Abstract: In this paper we investigate the electronic structure of Zn 1-x Co x O by means of optical absorption measurements under pressure. Thin films of Zn 1-x Co x O with different Co content (from 1 to 30%) were prepared by pulsed laser deposition on mica substrates. Absorption spectra exhibit three main features that are clearly correlated to the Co content in the films: (i) absorption peaks in the infrared associated to crystal-field-split internal transitions in the Co 3d shell, with very small pressure coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Recently, it has been shown that the pressure of the wurtzite-to-rock-salt transformation decreases for Co-and Mn-doped ZnO as compared to pure ZnO [7][8][9]. The high pressure -high temperature (HPHT) synthesis of ZnO-rich rs solid solutions Mn 0.25 Zn 0.75 O and Co 0.27 Zn 0.73 O in the form of thin films has been reported [8,9], however, in the case of bulk samples the situation may be different.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that the pressure of the wurtzite-to-rock-salt transformation decreases for Co-and Mn-doped ZnO as compared to pure ZnO [7][8][9]. The high pressure -high temperature (HPHT) synthesis of ZnO-rich rs solid solutions Mn 0.25 Zn 0.75 O and Co 0.27 Zn 0.73 O in the form of thin films has been reported [8,9], however, in the case of bulk samples the situation may be different.…”
Section: Introductionmentioning
confidence: 99%
“…This effect should be especially pronounced in diamond-like direct-bandgap semiconductors of n-А 3 В 5 and n-А 2 В 4 С 5 2 families, which is caused by, alongside with a χ(Р) dependence, a noticeable m n (P) dependence. As has been mentioned above, a sharp decrease of the resistivity by some orders of magnitude is observed, which testifies to the presence of the phase transition from diamond to NaCltype structure at P > 9 GPa [5,6]. According to formulas derived in the framework of the 'heterophase structureeffective medium' model [12], the relative volume fractions of the phases in the vicinity of the critical region of the polymorphous transformation (Fig.…”
mentioning
confidence: 67%
“…[1]) make the studies of the electron spectrum and charge transport of this compound of current importance. Nevertheless, data on electron transport phenomena at atmospheric and hydrostatic pressures obtained for bulk crystals are still not sufficient (see [1][2][3][4][5][6] and references therein). Earlier in [7], the kinetic properties of charge carriers in ZnO bulk crystals had been investigated depending on temperature (77-400 K at atmospheric pressure) and hydrostatic pressure up to P = 7 GPa at 300 K. In the present work these investigations are continued, being supplemented with measurements of the resistivity at quasihydrostatic pressure up to P = 25 GPa at T = 300 K.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both effects are correlated and the pressure beyond which they appear is smaller for larger Co concentrations. When OD ≤ 2, the shape of the CTT and the direct interband absorption edge becomes similar in NPs and thin films, 39 indicating that the effective W− Zn 1−x Co x O contents in the platelets is about the same order as in 150 nm thick thin films.…”
mentioning
confidence: 97%